Evaluation of Holy Quran & Islamic Education Curriculum of Second Intermediate Stage from Perspectives of Teachers & Supervisors of the Material:A Field Study conducted in the Directorates-General of Education in Baghdad Governorate: أشواق عبـد الحـسن عبـد (Journal of the College of Education for Women, 2020)
Evaluation of “Holy Quran & Islamic Education” Curriculum for Second Intermediate Stage from Perspectives of Teachers & Supervisors of material A Field Study conducted in the Directorates-General of Education in Baghdad Governorate. It goes without saying that educational curricula for students of all stages of schooling are in bad need of reviewing, evaluation and revision. The Islamic education curriculum is no exception, since it is a basic subject that plays a role in developing the individual’s moral and conscientious aspects, promotes his/her inner discipline and helps establish coherence with the values system of the community to which he/she belongs.Based on the foregoing, the evaluation process of the Islamic education curriculum may indicate points of strength or weakness, besides other results, conclusions and recommendations that may develop this method in the service of the educational process and contribute to building students up educationally and morally to qualify them to take their social roles in society.The study comes up with a set of results and conclusions which uncover the points of strength and weakness in the curriculum of “Holy Quran & Islamic Education” for the second intermediate stage, and backed them with a set of suggestions and recommendations, including:Conduct studies on the evaluation and revision of the curricula as a whole.refrain from any of the quotas adopted in the current book. Such tendencies inflame divisions.focus on the rulings of transactions according to the Islamic jurisprudence, which will help create good citizens.